Anthocyanins Promote Learning through Modulation of Synaptic Plasticity Related Proteins in an Animal Model of Ageing - David Vauzour; Catarina Rendeiro; Alfonsina D'Amato; Pierre Waffo-Téguo; Tristan Richard; Jean Michel Mérillon; Matthew G. Pontifex; Emily Connell; Michael Müller; Laurie T. Butler; Claire M. Williams; Jeremy P. E. Spencer (MDPI AG, 2021)
Anthocyanin-rich foods, such as berries, reportedly ameliorate age-related cognitive deficits in both animals and humans. Despite this, investigation into the mechanisms which underpin anthocyanin-mediated learning and memory benefits remains relatively limited. The present study investigates the effects of anthocyanin intake on a spatial working memory paradigm, assessed via the cross-maze apparatus, and relates behavioural test performance to underlying molecular mechanisms. Six-week supplementation with pure anthocyanins (2% w/w), administered throughout the learning phase of the task, improved both spatial and psychomotor performances in aged rats. Behavioural outputs were accompanied by changes in the expression profile of key proteins integral to synaptic function/maintenance, with upregulation of dystrophin, protein kinase B (PKB/Akt) and tyrosine hydroxylase, and downregulation of apoptotic proteins B-cell lymphoma-extra-large (Bcl-xL) and the phosphorylated rapidly accelerated fibrosarcoma (p-Raf). Separate immunoblot analysis supported these observations, indicating increased activation of extracellular signal-related kinase (ERK1), Akt Ser473, mammalian target of rapamycin (mTOR) Ser2448, activity-regulated cytoskeleton-associated protein (Arc/Arg 3.1) and brain-derived neurotrophic factor (BDNF) in response to anthocyanin treatment, whilst α-E-catenin, c-Jun N-terminal kinase (JNK1) and p38 protein levels decreased. Together, these findings suggest that purified anthocyanin consumption enhances spatial learning and motor coordination in aged animals and can be attributed to the modulation of key synaptic proteins, which support integrity and maintenance of synaptic function.